The 3′→5′ exonuclease of DNA polymerase δ can substitute for the 5′ flap endonuclease Rad27/Fen1 in processing Okazaki fragments and preventing genome instability - Jin, Yong Hwan (The National Academy of Sciences, 2001)
Many DNA polymerases (Pol) have an intrinsic 3′→5′ exonuclease (Exo) activity which corrects polymerase errors and prevents mutations. We describe a role of the 3′→5′ Exo of Pol δ as a supplement or backup for the Rad27/Fen1 5′ flap endonuclease. A yeast rad27 null allele was lethal in combination with Pol δ mutations in Exo I, Exo II, and Exo III motifs that inactivate its exonuclease, but it was viable with mutations in other parts of Pol δ. The rad27-p allele, which has little phenotypic effect by itself, was also lethal in combination with mutations in the Pol δ Exo I and Exo II motifs. However, rad27-p Pol δ Exo III double mutants were viable. They exhibited strong synergistic increases in CAN1 duplication mutations, intrachromosomal and interchromosomal recombination, and required the wild-type double-strand break repair genes RAD50, RAD51, and RAD52 for viability. Observed effects were similar to those of the rad27-null mutant deficient in the removal of 5′ flaps in the lagging strand. These results suggest that the 3′→5′ Exo activity of Pol δ is redundant with Rad27/Fen1 for creating ligatable nicks between adjacent Okazaki fragments, possibly by reducing the amount of strand-displacement in the lagging strand.